Growth and Performance of Melon (Cucumis melo L) in Respect of Payments and Fruit Trimming - Narita Amni Rosadi; Rosalina Edy Swandayani; Baiq Inggar Linggarweni (Postgraduate, University of Mataram, 2024)
This study used a completely randomized design (CRD), factorial with 2 intervention factors: M0 = 0 g/tree, M1 = 40 g/tree, M2 = 80 /tree. The second factor of fruit pruning (P), P0 = no size, P1 = remaining 1 fruit, P2 = remaining two fruits. This study was organized according to a 3x3 factorial design. Treatments were repeated three times and resulted in 27 experiments. The parameters observed included: Tree height, number of leaves, number of flowers, fruit weight, fruit diameter. Observation of plant growth will be done within 7 days after planting. Analysis using variance fingerprints. If there are significant differences between treatments, do the BNJ test at the 5% level. From the results of the analysis of variance in the table above shows that the application of organic fertilizer does not give a real effect on the height of the tree at the age of 70 hst, the number of leaves, fruit weight and diameter. Pruning treatment gives a real effect on the parameters of plant height after 70 days of planting, but does not give a real effect on the number of leaves, fruit weight and diameter